Defect Engineering in A2BO4 Thin Films via Surface‐Reconstructed LaSrAlO4 Substrates. Issue 11 (17th October 2022) - Kim, Jinkwon; Kim, Youngdo; Mun, Junsik; Choi, Woojin; Chang, Yunyeong; Kim, Jeong Rae; Gil, Byeongjun; Lee, Jong Hwa; Hahn, Sungsoo; Kim, Hongjoon; Chang, Seo Hyoung; Lee, Gun‐Do; et al.
Abstract: Ruddlesden–Popper oxides ( A 2 B O4 ) have attracted significant attention regarding their potential application in novel electronic and energy devices. However, practical uses of A 2 B O4 thin films have been limited by extended defects such as out‐of‐phase boundaries (OPBs). OPBs disrupt the layered structure of A 2 B O4, which restricts functionality. OPBs are ubiquitous in A 2 B O4 thin films but inhomogeneous interfaces make them difficult to suppress. Here, OPBs in A 2 B O4 thin films are suppressed using a novel method to control the substrate surface termination. To demonstrate the technique, epitaxial thin films of cuprate superconductor La2‐ x Sr x CuO4 ( x  = 0.15) are grown on surface‐reconstructed LaSrAlO4 substrates, which are terminated with self‐limited perovskite double layers. To date, La2‐ x Sr x CuO4 thin films are grown on LaSrAlO4 substrates with mixed‐termination and exhibit multiple interfacial structures resulting in many OPBs. In contrast, La2‐ x Sr x CuO4 thin films grown on surface‐reconstructed LaSrAlO4 substrates energetically favor only one interfacial structure, thus inhibiting OPB formation. OPB‐suppressed La2‐ x Sr x CuO4 thin films exhibit significantly enhanced superconducting properties compared with OPB‐containing La2‐ x Sr x CuO4 thin films. Defect engineering in A 2 B O4 thin films will allow for the elimination of various types of defects in other complex oxides and facilitate next‐generation quantum device applications. Abstract : Despite the tremendous potential for A 2 B O4 in high‐performance electronic/energy devices, A 2 B O4 film growth suffers from extended defects, i.e., out‐of‐phase boundaries (OPBs). OPB suppression is presented in A 2 B O4 films via substrate termination engineering. The single‐terminated LaSrAlO4 substrate enabled a homogenous interfacial structure of La2‐ x Sr x CuO4 films, resulting in significantly enhanced superconductivity. Our method contributes to the comprehensive utilization of oxide‐based functional devices.